SCONUL Research Extra - Hall, John (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
SCONUL Research Extra is a cooperative access and borrowing scheme for staff and research students in UK and Irish higher education institutions. Under the terms of the scheme, eligible researchers may visit any participating library and register as an external borrower. The scheme is run on behalf of SCONUL, the Society of College, National and University Libraries which represents the directors of the library and information services in all the universities of the United Kingdom and Ireland, and in most other UK institutions of higher education, and the directors of the national libraries; it is for all institutions in membership of SCONUL able to lend library materials and, with 158 institutions signed up, it is now the largest reciprocal borrowing scheme in the UK and Ireland, serving almost the entire membership of SCONUL.